A sequence of polynomials f k ( x ) is defined as follows. f 0 ( x ) = 1 ; f k + 1 ( x ) = f k ( x + 1 ) + x k + 1 , k = 0 , 1 , 2 , . . . Find the last 3 digits of the coefficient of x in f 1 0 ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I claim that for every positive integer n ,
f n ( x ) = i = 0 ∑ n ( x + i ) n − i
We will prove this by induction.
The base case n = 0 trivially holds, so let us now assume that f n ( x ) = ∑ i = 0 n ( x + i ) n − i holds for some n . Replacing x with x + 1 gives f n ( x + 1 ) = ∑ i = 0 n ( x + 1 + i ) n − i . Then f n + 1 ( x ) = = = f n ( x + 1 ) + x n + 1 x n + 1 + i = 0 ∑ n ( x + 1 + i ) n − i i = 0 ∑ n + 1 ( x + i ) n + 1 − i , and our induction is complete.
Thus for the case of n = 1 0 , we have f 1 0 ( x ) = x 1 0 + ( x + 1 ) 9 + ( x + 2 ) 8 + ( x + 3 ) 7 + ⋯ + ( x + 9 ) + 1 By the Binomial Theorem, the coefficient of x is 1 8 ⋅ 9 + 2 7 ⋅ 8 + 3 6 ⋅ 7 + ⋯ + 9 1 ⋅ 1 + 1 = 1 6 4 3 3 The requested answer is 4 3 3 .
In order to find the coefficient of x we need to iterate the formula until we obtain a plain formula: f 1 0 ( x ) = f 9 ( x + 1 ) + x 1 0 = f 8 ( x + 2 ) + ( x + 1 ) 9 + x 1 0 = f 7 ( x + 3 ) + ( x + 2 ) 8 + ( x + 1 ) 9 + x 1 0 = f 6 ( x + 4 ) + ( x + 3 ) 7 + ( x + 2 ) 8 + ( x + 1 ) 9 + x 1 0
. . .
= f 0 ( x + 1 0 ) + ( x + 9 ) 1 + ( x + 8 ) 2 + ( x + 7 ) 3 + ( x + 6 ) 4 + ( x + 5 ) 5 + ( x + 4 ) 6 + ( x + 3 ) 7 + ( x + 2 ) 8 + ( x + 1 ) 9 + x 1 0 = 1 + ( x + 9 ) 1 + ( x + 8 ) 2 + ( x + 7 ) 3 + ( x + 6 ) 4 + ( x + 5 ) 5 + ( x + 4 ) 6 + ( x + 3 ) 7 + ( x + 2 ) 8 + ( x + 1 ) 9 + x 1 0
Now we perform the calculation of each term, just worrying about the x coefficient. For instance ( x + 9 ) 1 has x coefficient 1. And ( x + 8 ) 2 = x 2 + 2 × 8 1 × x + 6 4 has x coefficient 2 × 8 1 × x
Continuing all the calculations, we get:
1 × x + 2 × 8 1 × x + 3 × 7 2 × x + 4 × 6 3 × x + 5 × 5 4 × x + 6 × 4 5 × x + 7 × 3 6 × x + 8 × 2 7 × x + 9 × 1 8 × x
This results in 1 6 4 3 3 × x . This is the x coefficient we are looking for and the last 3 digits are 4 3 3 .
It can be easily observed by expansion that f n ( x ) = k = 0 ∑ n ( x + n − k ) k
In specific, f 1 0 ( x ) = k = 0 ∑ 1 0 ( x + 1 0 − k ) k
By binomial expansion, the coefficient of x is k = 2 ∑ 9 k ( 1 0 − k ) k − 1 , of which the last three digits are 433.
f 0(x) = 1 f 1(x) = 1 + x f 2(x) = 1 + (x+1) + x^2 f 3(x) = 1 + (x+2) + (x+1)^2 + x^3 f 4(x) = 1 + (x+3) + (x+2)^2 + (x+1)^3 + x^4 ... Continuing the pattern would show that: f 10(x) = 1 + (x+9) + (x+8)^2 + (x+7)^3 + ... + (x+2)^8 + (x+1)^9 + x^10 Using the Binomial Theorem, the coefficients of x for each expansion can be obtained. The coefficient of x in (x+9) is 1. The coefficient of x in (x+8)^2 is ( 2C 1)(8). The coefficient of x in (x+7)^3 is ( 3C 2)(7^2). The coefficient of x in (x+6)^4 is ( 4C 3)(6^3). The total sum can then be expressed as: \displaystyle \sum_{i=1}^9 (10-i)(i^(9-i)). Solving this expression gives the total of 16433. Therefore, the last 3 digits of the coefficient of x are 433.
We have f 0 ( x ) = 1 , f 1 ( x ) = x + 1 , f 2 ( x ) = x 2 + ( x + 1 ) + 1 , f 3 ( x ) = x 3 + ( x + 1 ) 2 + ( x + 2 ) 1 + 1 .... continuing so we have that f 1 0 ( x ) = x 1 0 + ( x + 1 ) 9 + ( x + 2 ) 8 + ( x + 3 ) 7 + ( x + 4 ) 6 + . . . . . . + ( x + 8 ) 2 + ( x + 9 ) 1 + 1 .
Each term has the form ( x + k ) 1 0 − k , k = 0 , 1 , 2 , . . . , 1 0 . The coefficient of x in each term is given by ( 1 0 − k ) k 1 0 − k − 1 due to the binomial teorem. The coefficient of x in f 1 0 ( x ) is given by the sum of the coefficient of each term. So it is given by: 9 ⋅ 1 8 + 8 ⋅ 2 7 + 7 ⋅ 3 6 + 6 ⋅ 4 5 + 5 ⋅ 5 4 + 4 ⋅ 6 3 + 3 ⋅ 7 2 + 2 ⋅ 8 1 + 1 . This is equal to 1 6 4 3 3 , so the last 3 digits are 4 3 3 .
note that:
f 0(x)=1 f 1(x)=1 + x f 2(x)=1 + (x+1) + (x)^2 f 3(x)=1 + (x+2) + (x+1)^2 + x^3 . . . . f_{10}(x)= 1 + (x+9) + (x+8)^2 + (x+7)^3 + (x+6)^4 + (x+5)^5 + (x+4)^6 +(x+3)^7 + (x+2)^8 + (x+1)^9 +x^{10}
and using the binomial theorem, we get the following coefficients of x of the the powers of (x+k), k=1,2,..10.
(x+9) =1 (x+8)^2=16 (x+7)^3=147 (x+6)^4=864 (x+5)^5=3125 (x+4)^6=6144 (x+3)^7=5103 (x+2)^8=1024 (x+1)^9=9 x^{10}=0
which is when you add, you will get 16433.
f 1 0 ( x ) = f 9 ( x + 1 ) + x 1 0 and f 9 ( x + 1 ) = f 8 ( x + 2 ) + ( x + 1 ) 9 and so on for f 8 ( x + 2 ) till f 1 ( x + 9 ) and f 0 ( x + 1 0 ) = 1
therefore f 1 0 ( x ) = x 1 0 + ( x + 1 ) 9 + ( x + 2 ) 8 + ( x + 3 ) 7 + ( x + 4 ) 6 + ( x + 5 ) 5 + ( x + 6 ) 4 + ( x + 7 ) 3 + ( x + 8 ) 2 + ( x + 9 ) 1 and sum coefficient of x in all the above terms will be:- 9 c 1 ∗ 1 + 8 c 1 ∗ 2 7 + 7 c 1 ∗ 3 6 + 6 c 1 ∗ 4 5 + 5 c 1 ∗ 5 5 + 4 c 1 ∗ 6 3 + 3 c 1 ∗ 7 2 + 2 c 1 ∗ 8 1 + 1 = 9 + 1 0 2 4 + 5 1 0 3 + 6 1 4 4 + 3 1 2 5 + 8 6 4 + 1 4 7 + 1 6 + 1 = 1 6 4 3 3 therefore the last 3 digits of the coefficient of x in f 1 0 ( x ) is 4 3 3 .
Just see the recursion... We get f10(x) = f9(x+1)+x^10=f8(x+2)+(x+1)^9+x^10=f7(x+3)+(x+2)^8+(x+1)^9+x^10=......(continue by yourself)=Ʃ(x+k)^(10-k) Using the binomial newton theorem, we can see Coefficient of x in (x+k)^(10-k) is (10-k) (k^(9-k)) So, we just find the value of \displaystyle \sum_{i=1}^3 (10-k) (k^(9-k)) And just a little work to count them we get 16433... And the last 3 digits of the coefficient of x is 433...
Keep rewriting f10, f9, f8, ..., until you reach f0. f10(x) = f9(x+1) + x^10 f9(x+1) = f8(x+2) + (x+1)^9 f8(x+2) = f7(x+3) + (x+2)^8 f7(x+3) = f6(x+4) + (x+3)^7 ... f3(x+7) = f2(x+8) + (x+7)^3 f2(x+8) = f1(x+9) + (x+8)^2 f1(x+9) = f0(x+10) + (x+9)^1 f0(x+10) = f0(x) = 1
Now, work your way back up and you'll get. f10(x) = x^10 + (x+1)^9 + (x+2)^8 + (x+3)^7 + ... + (x+8)^2 + (x+9)^1 +1 X coeff= 0 + 9 1^8 + 8 2^7 + 7 3^6 + 6 4^5 + ... + 2 8^1 + 1 9^0 X coeff= 16433
If you were confused by the above step, here is an example with calculating the coefficient of x in the (x+3)^7 term. (x+3)^7 = (x+3)(x+3)(x+3)(x+3)(x+3)(x+3)(x+3) In 6 of those terms, we need to multiply by a 3. In 1 of those terms, we need to multiply by a 1x. There are 7C1 ways to pick which factor gives the x. 7C1 * 3^6 * 1 = 5103
Define g k ( x ) to be the derivative of f k ( x ) . Then g 0 ( x ) = 0 and, differentiating the functional equation for f k + 1 , g k + 1 ( x ) = g k ( x + 1 ) + ( k + 1 ) x k
Note that the coefficient we are looking for is g 1 0 ( 0 ) . Applying the recursive formula for g 1 0 , g 9 and so on, we get: g 1 0 ( 0 ) = g 9 ( 1 ) + 1 0 ⋅ 0 9 = g 8 ( 2 ) + 9 ⋅ 1 8 + 1 0 ⋅ 0 9 = g 7 ( 3 ) + 8 ⋅ 2 7 + 9 ⋅ 1 8 + 1 0 ⋅ 0 9 = = . . . = g 0 ( 1 0 ) + ( 1 ⋅ 9 0 + 2 ⋅ 8 1 + . . . + 9 ⋅ 1 8 + 1 0 ⋅ 0 9 ) Because g 0 ( 1 0 ) = 0 , we just need to calculate the last three digits of the sum 1 ⋅ 9 0 + 2 ⋅ 8 1 + . . . + 9 ⋅ 1 8 + 1 0 ⋅ 0 9 . This sum is 1 + 1 6 + 3 ⋅ 4 9 + 4 ⋅ 6 3 + 5 ⋅ 5 4 + 6 ⋅ 4 5 + 7 ⋅ 3 6 + 8 ⋅ 2 7 + 9 + 0 = = 1 + 1 6 + 1 4 7 + 8 6 4 + 3 1 2 5 + 6 1 4 4 + 5 1 0 3 + 1 0 2 4 + 9 = 1 6 4 3 3 So the answer is 4 3 3 .
What is polynomial Recursion?
First observe that the coefficient of x in f 1 0 ( x ) is equal to f 9 ′ ( 1 ) . In fact if P ( x ) = a n x n + ⋯ a 1 x + a 0 then P ( x + 1 ) = a n ( x + 1 ) n + ⋯ + a 1 ( x + 1 ) + a 0 = a n x n + ⋯ + ( ( n − 1 n ) a n + ( n − 2 n − 1 ) a n − 1 + ⋯ + a 1 ) x + ( a 0 + a 1 + ⋯ + a n ) = a n x n + ⋯ + ( n a n + ( n − 1 ) a n − 1 + ⋯ + a 1 ) x + ( a 0 + a 1 + ⋯ + a n ) = and P ′ ( x ) = a n n x n + a n − 1 ( n − 1 ) x n − 1 + ⋯ + a 1 ⟹ P ′ ( 1 ) = n a n + ( n − 1 ) a n − 1 + ⋯ + a 1 . Now with this observation we just need to apply the derivative in the recurrence relation, use it with f 9 ′ ( 1 ) and complete taking ( m o d 1 0 0 0 ) f k + 1 ( x ) = f k ( x + 1 ) + x k + 1 f k + 1 ′ ( x ) = f k ′ ( x + 1 ) + ( k + 1 ) x k ⟹ f 9 ′ ( 1 ) = f 8 ′ ( 2 ) + 9 ⋅ 1 8 = f 7 ′ ( 3 ) + 9 ⋅ 1 8 + 8 ⋅ 2 7 = ⋯ = k = 1 ∑ 9 k 9 − k ( 1 0 − k ) ≡ 4 3 3 ( m o d 1 0 0 0 )
Problem Loading...
Note Loading...
Set Loading...
From the definition, we have f 1 0 ( x ) = f 9 ( x + 1 ) + x 1 0
But f 9 ( x + 1 ) = f 8 ( x + 2 ) + ( x + 1 ) 9 so f 1 0 ( x ) = f 8 ( x + 2 ) + ( x + 1 ) 9 + x 1 0 and f 8 ( x + 2 ) = f 7 ( x + 3 ) + ( x + 2 ) 8 so f 1 0 ( x ) = f 7 ( x + 3 ) + ( x + 2 ) 8 + ( x + 1 ) 9 + x 1 0 .
Continuing in this pattern, we reach f 1 0 ( x ) = f 0 ( x + 1 0 ) + ( x + 9 ) 1 + ( x + 8 ) 2 + … + ( x + 1 ) 9 + x 1 0
We are looking for the coefficient of x, which is the sum of the coefficients of x in the individual terms. Using the binomial theorem, we have the coefficient of x in ( x + 9 ) 1 as ( 1 1 ) 9 0 , the coefficient of x in ( x + 8 ) 2 as ( 1 2 ) 8 1 , that in ( x + 7 ) 3 as ( 1 3 ) 7 2 and in general, the coefficient of x in ( x + a ) 1 0 − a as ( 1 1 0 − a ) a 9 − a = ( 1 0 − a ) a 9 − a .
Therefore, our expression for the coefficient of x in the sum is 1 × 9 0 + 2 × 8 1 + 3 × 7 2 + … + 8 × 2 7 + 9 × 1 8
We must take the the last 3 digits in the sum, which can be done by taking the last 3 digits in the individual terms, so our sum becomes 1 + 1 6 + 1 4 7 + 8 6 4 + 1 2 5 + 1 4 4 + 1 0 3 + 2 4 + 9 = 1 4 3 3
The last 3 digits of that is 4 3 3 , our answer.